Determining The Concentration Level of Some Elements Caused by Geological Period in The Sediments of Lake Hazar - Özgür Canpolat; Kürşad Kadir Eriş; Eyyüp Önder Akkoyun (Turkish Journal of Agriculture: Food Science and Technology)
In this study, it was aimed to determine the concentrations of some elements in sediment along depht profile in core collected at the Lake Hazar (Elazıg) and to compared the results according to recent geological periods. For this purpose, the levels of arsenic (As), mercury (Hg), molybdenum (Mo), barium (Ba), uranium (U), tin (Sn), titanium (Ti), lanthanum (La) and beryllium (Be) on every 5 cm of the piston core samples taken as part of a TUBİTAK project (No: 111Y045) from Lake Hazar were detected. The lowest concentrations of Ba, Hg, La, Ti and U were found (111 ppm, 0.01 ppm, 4.4 ppm, 1190 ppm and 0.6 ppm respectively) at 81-83 cm in depth. It was determined that it belonged to 10 000 B.P. and to Holocene Period (10.5 thousand B.P.). The highest concentrations of As, Ba, Hg, Sn, La, Mo, Ti and U were found different depth in the core in Lake Hazar. The highest concentrations of Hg in the core were detected between 4-6 cm that this depth was determined corresponds to present day. The highest levels of As and Ba found that it belonged to Pre-Glacial Period/ Late Pleistocene Period (10.5 thousand B.P.). The highest concentration of other elements (Sn, La, Mo and Ti) determined that it belonged to Last Glacial Maximum Period/Late Pleistocene Period (between 23-16 thousand B.P.). The geological structure of the basin where the lake ecosystem is located, biological and hydrological processes, climatic and anthropogenic factors can be cited as the reasons for these differences.